Deep Learning Approach In PAI Learning In An Effort To Transform The Understanding Of The Alpha Generation - Yusron Nur Hadi; Ikhrom Ikhrom; Mahfud Junaedi; Fihris Fihris; Nurul Laely Mahmudah (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2026)
The low level of students’ understanding in Islamic religious education has often been attributed to the influence of digital technology; however, this study reveals that the primary issue lies in the inadequacy of pedagogical approaches employed in the learning process. This study aims to analyse the role of the deep learning approach as a transformative pedagogical framework in enhancing conceptual understanding and the internalisation of religious values among Generation Alpha learners. The significance of this research is grounded in the mismatch between conventional teacher-centred learning and the characteristics of Generation Alpha, who require interactive, reflective, and contextual learning experiences. This research adopts a qualitative approach, using a library research method to analyse relevant scholarly sources. It assumes that meaningful, mindful, and student-centred learning can foster deeper understanding. The findings indicate that the deep learning approach effectively transforms learning from memorisation into meaningful understanding through reflective activities, active participation, and contextual engagement. This study contributes by positioning deep learning as a comprehensive pedagogical paradigm in Islamic religious education. Therefore, transforming instructional design is essential to improving students’ understanding in the digital era.